2024
DOI: 10.3390/s24030950
|View full text |Cite
|
Sign up to set email alerts
|

Maritime Emission Monitoring: Development and Testing of a UAV-Based Real-Time Wind Sensing Mission Planner Module

Theodoros Karachalios,
Panagiotis Moschos,
Theofanis Orphanoudakis

Abstract: Maritime emissions contribute significantly to global pollution, necessitating accurate and efficient monitoring methods. Traditional methods for tracking ship emissions often face limitations in real-time data accuracy, with wind measurement being a critical yet challenging aspect. This paper introduces an innovative mission planner module for unmanned aerial vehicles (UAVs) that leverages onboard wind sensing capabilities to enhance maritime emission monitoring. The module’s primary objective is to assist op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…On the other hand, in atmospheric pressure and wind direction there is hardly any difference. Other authors also found wind measurement being a critical challenging aspect [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in atmospheric pressure and wind direction there is hardly any difference. Other authors also found wind measurement being a critical challenging aspect [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, Mission Planner is used as the flight planning and simulation program. Furthermore, the quadrotor dynamics [19] required for flight are provided by embedded libraries in the Mission Planner open source software [20].…”
Section: Methodsmentioning
confidence: 99%
“…An exploration of evolutionary algorithms in enhancing the design and problem-solving capabilities of swarm robotics is presented in [17]. The article in [18] demonstrates the innovative applications of swarm robotics in theoretical and practical domains. Distributed collaborative partial SLAM for efficient navigation of autonomous robots [19] and the development of control algorithms for group formation flights in dense environments [20] can improve coordination within drone swarms.…”
Section: Introductionmentioning
confidence: 99%